Gingival condition of patient with obesity - Alyani, Atikah Sabrina; Wendari, Sri; Hadidjah, Dede (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2012)
The prevalence of obesity has increased drastically in most developed countries. Many studies showed that obesity associated with oral diseases, especially periodontal disease. A recent study showed the relation between WC and periodontal disease counted by gingival index (GI). However, studies regarding the mechanism of the relationship between obesity and periodontal disease are still quite a few, whereas many studies conducted suggested that obesity was a medical problem. The study was aimed to know and assess the gingival condition of obese people who visited the Dental Polyclinic of Hasan Sadikin Hospital. The type of this study was descriptive with the survey technique. A total of 54 people consisted of 35 female and 19 male patients with the age range of 20-49 years old, and not using any dental prosthesis or orthodontic appliance. This study was using a questionnaire and clinical examination to assess the condition of the gingival using the LÃ¶e and Silness Gingival index (GI). Examination of obesity conducted by measuring the waist circumference with criteria from WHO. The average value of the gingival index was 1.22. Meanwhile, the average value of the waist circumference (WC) was 95.89 cm and 107.74 cm consecutively for female and male. The majority of obese patients suffered moderate gingivitis.